“Every Word in Your Commentary Sounds Like Poetry”: Hotel Managers’ Responses to Customer Reviews Published on TripAdvisor - Tereszkiewicz, Anna (Media - Culture - Social Communication, 2019)
This study is devoted to responses to hotel reviews published by customers on TripAdvisor. The form of the reaction to customers’ opinions is significant in the process of creating and maintaining a positive image of a hotel. The aim of the analysis was to investigate the basic genre properties of the responses, i.e. their structural and pragmatic features. The analysis covered responses to both positive and negative reviews. The study showed that the components of review responses comprise, among others, address forms, expressions of gratitude, apologies, explanations, promises to undertake corrective actions, acts of advice and recommendation, as well as acts undermining the negative opinion expressed by the client. The study discusses the stylistic shape of selected speech acts used in the responses as well. The analysis, conducted with reference to the results of previous studies in other cultural contexts, points to universal components of the genre and properties typical of Polish responses.